Case-Control Study: Evaluation of the Correlation between Obesity and Hypertension in South Jakarta Adolescents - Ivana Ester Sinta Uli; Nurhayati Adnan Prihartono (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: The prevalence of hypertension in adolescents has increased in recent years. Initially, hypertension was rare in adolescents, but now hypertension is showing a trend of prevalence at a younger. Hypertension in adolescents is multifactorial, and there is no single cause. However, some studies suggest that high blood pressure or hypertension is more common in overweight or obese adolescents. Objective: To determine the correlation between obesity and hypertension in adolescents in South Jakarta in 2023. Method: This research is an analytical study with a case-control design, using secondary data from the Non-Communicable Disease Information System (SIPTM) of DKI Jakarta Provincial Health Office in 2023. The sample size used the Lemeshow formula, hypothesis tests for two proportions (two-sided test), with 1124 respondents divided by 562 cases and 562 controls, by purposive sampling technique. Statistical tests included univariate, stratification, and multivariate analysis (logistic regression causal model).. Result: The obesity proportion was 29.8%, primarily female, at 58.45%, with the highest being 16 years (25.8%). After evaluating confounding, found a significant correlation between obesity and hypertension in adolescents, namely aOR 3,6 (95% CI 2.72 - 4.73), which means that obese adolescents are statistically proven to have a 3,6 times greater risk of developing hypertension than non-obese adolescents. Conclusion: This finding indicates a prevalence increase of hypertension in the future if there is no obesity control in adolescents. Need screening or early detection in adolescents, especially in obese adolescents. Hypertension screening in adolescents to involve parents so that they get enough attention in the screening routine. In addition, there will be collaborative efforts between schools and healthcare providers to provide education and health promotion for school children, especially adolescents, to control hypertension and other non-communicable diseases.